Soft colloids in confinements - Sankaewtong, Krongtum (Nanyang Technological University, 2020)
Colloids are ubiquitous in nature, e.g. dust, milk or blood and also exist as daily life products, e.g paints, jelly or whipped cream. Thus, better understanding of behaviors of colloidal systems can draw paths to advancement in technologies and innovation. By confining colloidal dispersions, the systems exhibit richer phase behaviors compared to their three-dimensional bulk counterparts. For example, in the simplest model of hard spheres system, the confinement induces a phase transition between triangular(Δ) and square(□) symmetries with a sequence of ...nΔ → (n+1)□ → (n+1)Δ... ,where n is the number of crystal layers, which is a function of confinement height out of the FCC phase of the bulk system.